PERANAN PENGENDALIAN INTERNAL PIUTANG USAHA DALAM MEMINIMALKAN KERUGIANPADA PT. FIF POS CURUP - Elfison Dahsananranca Syawtupan (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstrack-This research is to know how the role of Internal control receivable in PT. FIF Pos Curup in minimizing loss of business receivables. The analysis used in this study is a qualitative descriptive analysis method.The results of the research can be concluded that the internal control of PT. FIF Pos Curup has not been applied properly in minimizing the bad credit, this is because the estimated amount of credit is jammed every year there is still an increase in the year 2018 is caused by several factors such as internal factors and external factors, internal factors due to the control environment still using the family system and also External factors are influenced by two aspects of the economic aspect that affects the bad credit when not yet before the harvest season in the community and cultural aspects such as the existence of the celebration of Eid al-Fitr and Eid al-Adha